Brazil and Paraguay: border specificity in pedagogical practices and current legislation (Práxis Educativa, 2024)
In this article, education in a border region is analyzed, with a special focus on the geographic context of Ponta Porã, Mato Grosso do Sul, Brazil, and Pedro Juan Caballero, Paraguay. The main objective was to investigate how the challenges, resulting from the cultural diversity that characterizes this geographic space, are addressed in official documents of the Brazilian education and whether such documents guarantee due attention to the particularities of education in the border regions of Brazil and Paraguay. To this end, the research question was: Do official documents guarantee compliance with the specificities present in border education between Brazil and Paraguay? The work was divided into three sections. In the first, the concept of border and the local reality of the research region are addressed. In the second, information about regionalism in official documents is provided. In the final section, two pedagogical proposals from state schools in Ponta Porã are analyzed, in order to verify whether they contain records related to the border reality of the region. It became evident from the study carried out that the official documents that govern the Brazilian education, at all government levels, need to consider, in their writing, regionalism and the specificities of each region, or, even, ensure that states and municipalities deal in its regulations its particularities. This implies ensuring that state and municipal regulations reflect their own realities, representing a call for responsibility on the part of states and municipalities in developing education policies aligned with their specific needs.Keywords: Education policies. Frontier education. Official documents.